2002
DOI: 10.1210/jc.2002-020568
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin 4 Receptor Sequence Variations Are Seldom a Cause of Human Obesity: The Swedish Obese Subjects, the HERITAGE Family Study, and a Memphis Cohort

Abstract: The prevalence of mutations within and in the flanking regions of the gene encoding the melanocortin 4 receptor was investigated in severely obese and normal-weight subjects from the Swedish Obese Subjects study, the Health, Risk Factors, Exercise Training, and Genetics (HERITAGE) Family study, and a Memphis cohort. A total of 433 white and 95 black subjects (94% females) were screened for mutations by direct sequencing. Three previously described missense variants and nine novel (three missense, six silent) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 32 publications
6
62
1
3
Order By: Relevance
“…Thus, the prevalence of loss-of-function MC4R mutations in our large sample set of obese subjects of European origin is 1.72%. Although our mode of recruitment of obese patients may have tended to overestimate the proportion of severe phenotypes, the prevalence is consistent with that previously published in other obese cohorts (14,18,(33)(34)(35). Our findings in the control cohort are consistent with other large, population-based cohorts (6), such as the KORA-S4 study, where the prevalence of MC4R mutations was also 0.15%.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the prevalence of loss-of-function MC4R mutations in our large sample set of obese subjects of European origin is 1.72%. Although our mode of recruitment of obese patients may have tended to overestimate the proportion of severe phenotypes, the prevalence is consistent with that previously published in other obese cohorts (14,18,(33)(34)(35). Our findings in the control cohort are consistent with other large, population-based cohorts (6), such as the KORA-S4 study, where the prevalence of MC4R mutations was also 0.15%.…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, more than 30 different mutations, including missense, nonsense, and frameshift mutations, in the MC4R gene have been reported in French, English, German, American, Italian, and Spanish individuals. [31][32][33][34][35][36][37][38][39][40][41][42][43] Functional studies showed that many of the missense mutations, and all three frameshift mutations described so far, led to a complete or partial loss of function of the MC4R gene. 31,33,40,42,44,45 In a recent study, Farooqi et al 42 found that the signaling properties of mutant MC4R receptors, as determined in cell The inactivity score is adjusted for sex, age, and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The first SNP, rs34114122 (A/C), was located at the 5'-UTR of the promoter site in the MC4R gene and has been previously reported in European, American, and Asian populations (Jacobson et al, 2002;Lubrano-Berthelier et al, 2003;Stutzmann et al, 2007;Van Den Berg et al, 2011;Tan et al, 2014). This variant was not found to be associated with obesity.…”
Section: Discussionmentioning
confidence: 89%